PL.35 Outcomes Following Induction of Labour(IOL) in the East of Scotland. (26th April 2013) - Fawzy, M; Balakumar, V; Nicoll, AE
Abstract : Objectives: To review delivery outcomes for IOL at Term in Ninewells Hospital Dundee and to determine whether maternal factors, indications and gestational age influence outcomes. Methods: Data were collected from all IOL at Term between 01/01/11–31/08/12. Information on outcomes was collected from the local maternity database (Torex Protos Evolution). Results: 1802/7499 (24%) had IOL. Median age was 29 years (Range = 15–48 years) and median BMI was 25.7 kg/m2 (Range = 15–66 kg/m2). 1020/1802 (56.6%) were primiparous. Median gestational age was 40 weeks (Range 37–43 weeks). 664/1802 (36.8%) of IOL were for post-dates pregnancy, 280/1802 (15.5%) were for prolonged pre-labour rupture of membranes (PROM), 194/1802 (10.7%) were for hypertensive disease, 132/1802 (7.3%) were for suspected fetal growth restriction (FGR) and 106/1802 (5.8%) were for diabetes.1057/1802 (58.6%) had spontaneous vertex delivery, 360/1802 (19.9%) had operative vaginal; delivery (OVD) and 385/1802 (21.3%) had caesarean section (CS). BMI > 30 kg/m2 was associated with increased risk of CS (RR = 1.23.95%CI = 1.01–1.50, p = 0.03), and this was independent of gestational age and indication. Women who had IOL for post dates pregnancy had higher rates of CS (RR = 1.25.95%CI = 1.05–1.50, p = 0.01) and OVD (RR = 1.28.95%CI = 1.06–1.54, p = 0.01). Women who had IOL for suspected SGA fetus had lower rates of CS (RR = 0.51, 95%CI = 0.31–0.83, p = 0.003) Women who had IOL for PROM had lower rates of OVD (RR = 0.57, 95%CI = 0.43–0.76, p < 0001). Conclusion: The majority of women who have IOL at Term will have a vaginal delivery. Nevertheless the risk of operative intervention increases significantly in women who have IOL at 41 weeks gestation and beyond. due to IOL for post dates pregnancy. This data will be useful in counselling women requiring IOL at Term.